High Plasma Levels of sTNF-R1 and CCL11 Are Related to CD4+ T-Cells Fall in Human Immunodeficiency Virus Elite Controllers With a Sustained Virologic Control - Gutiérrez-Rivas, Mónica; Jiménez-Sousa, María Ángeles; Rallón, Norma; Jiménez, José Luis; Restrepo, Clara; León, Agathe; Montero-Alonso, Marta; González-García, Juan; Muñoz-Fernández, María Ángeles; Benito, José Miguel; Resino, Salvador; , on Behalf of ECRIS Integrated in the Spanish AIDS Research Network (Frontiers in Immunology, 2018)
Our aim was to analyze the relationship between plasma inflammatory biomarkers and CD4+ T-cells evolution in HIV elite controllers (HIV-ECs) with a suppressed viremia. We carried out a retrospective study in 30 HIV-ECs classified into two groups: those showing no significant loss of CD4+ T-cells during the observation period (stable CD4+, n=19) and those showing a significant decrease of CD4+ T-cells (decline CD4+, n=11). Baseline plasma biomarkers were measured using a multiplex immunoassay: sTNF-R1, TRAIL, sFas (APO), sFasL, TNF-α, TNF-β, IL-8, IL-18, IL-6, IL-10, IP-10, MCP-1, MIP-1α, MIP-1β, RANTES, SDF1α, GRO-α, and CCL11. Baseline levels of sTNF-R1 and CCL11, and sTNF-R1/TNF-α ratio correlated with the slope of CD4+ T-cells (cells/µl/year) during follow-up [r=-0.370 (p=0.043), r=-0.314 (p=0.091), and r=-0.381 (p=0.038); respectively]. HIV-ECs with declining CD4+ T-cells had higher baseline plasma levels of sTNF-R1 [1500.7 (555.7; 2060.7) pg/ml vs. 450.8 (227.9; 1263.9) pg/ml; p=0.018] and CCL11 [29.8 (23.5; 54.9) vs. 19.2 (17.8; 29.9) pg/ml; p=0.041], and sTNF-R1/TNF-α ratio [84.7 (33.2; 124.2) vs. 25.9 (16.3; 75.1); p=0.012] than HIV-1 ECs with stable CD4+ T-cells. The area under the receiver operating characteristic curve (AUROC) were 0.758±0.093 (sTNF-R1), 0.727±0.096 (CCL11), and 0.777±0.087 (sTNF-R1/TNF-α). The cut-off of 75th percentile (high values) for these biomarkers had 71.4% positive predictive value and 73.9% negative predictive value for anticipating the evolution of CD4+ T-cells. In conclusion, the loss of CD4+ T-cells in HIV-ECs was associated with higher levels of two plasma inflammatory biomarkers (sTNF-R1 and CCL11), which were also reasonably accurate for the prediction of the CD4+ T-cells loss.